1995
DOI: 10.1021/cm00054a026
|View full text |Cite
|
Sign up to set email alerts
|

Photorefractive Polymer with Side-Chain Second-Order Nonlinear Optical and Charge-Transporting Groups

Abstract: We report the synthesis and characterization of a new, low-T, polymer exhibiting the photorefractive effect. The photorefractive polymer contains a second-order nonlinear optical chromophore, a charge transporting group, and a long aliphatic chain covalently linked to the polymer backbone. A sensitizer (CSO) was molecularly doped into the polymer to facilitate photocharge generation. The photoconductivity, electrooptic (Pockels) effect, and photorefractive properties of the polymer are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 1 publication
1
48
0
Order By: Relevance
“…From a practical point of view, the optical amplification, Γ, must exceed the absorption loss, R, of the PR sample in question. [37][38][39] In this case, the optical loss of the sandwiched sample (glass/ITO/polymer composite/ITO/glass) at 1.31 µm was measured to be R ) 4.2 cm -1 yielding a maximum net gain coefficient of Γ -R ) 30.9 cm -1 . An example of asymmetric exchange of energy is depicted in the inset in Figure 3, which confirms the PR nature of the NCPbS composite.…”
Section: Resultsmentioning
confidence: 93%
“…From a practical point of view, the optical amplification, Γ, must exceed the absorption loss, R, of the PR sample in question. [37][38][39] In this case, the optical loss of the sandwiched sample (glass/ITO/polymer composite/ITO/glass) at 1.31 µm was measured to be R ) 4.2 cm -1 yielding a maximum net gain coefficient of Γ -R ) 30.9 cm -1 . An example of asymmetric exchange of energy is depicted in the inset in Figure 3, which confirms the PR nature of the NCPbS composite.…”
Section: Resultsmentioning
confidence: 93%
“…These results of the effect of T g on the PR properties is the first report for the single component system to the best of our knowledge. Zhao et al [19] reported a low diffraction efficiency of 1% and gain coefficient of 10 cm À1 for the copolymer containing carbazole unit, which had T g at 47°C. For their system a higher T g may be the reason for the low PR properties.…”
Section: Resultsmentioning
confidence: 99%
“…The other approach is the utilization of side-chain polymers in which each component is chemically attached on the side chain to offer the structural flexibility of NLO moiety relative to the main-chain polymers [17±19]. Zhao et al [19] reported PR materials consisting of the methacrylate polymer containing a carbazole unit and a stilbene derivative in the side chain. They also introduced an octylmethacrylate as a comonomer to decrease T g , to enhance the structural flexibility.…”
mentioning
confidence: 99%
“…2-Aminothiophenol, 4-methylcinnamic acid, and 2-thiophenecarbaldehyde (4Ј) were obtained from Acros Ltd. 4-(Diethylamino)benzaldehyde (1Ј) and 4-(N-carbazolyl)benzaldehyde (3Ј) were synthesized according to a literature procedure. [25] 4-(Diphenylamino)benzaldehyde (2Ј) was prepared by a standard Vilsmeier reaction. All the solvents used for absorption and fluorescence measurements were HPLC grade.…”
Section: Methodsmentioning
confidence: 99%